2015
DOI: 10.1371/journal.pntd.0003743
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Nutritional Status and Malaria in Children from a Rural Community in the Amazonian Region: A Longitudinal Study

Abstract: BackgroundThe relationship between malaria and undernutrition is controversial and complex. Synergistic associations between malnutrition and malaria morbidity and mortality have been suggested, as well as undernutrition being protective against infection, while other studies found no association. We sought to evaluate the relationship between the number of malaria episodes and nutritional statuses in a cohort of children below 15 years of age living in a rural community in the Brazilian Amazon.Methodology/Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 33 publications
3
48
2
4
Order By: Relevance
“…These findings are similar to those of many other studies, which have reported that malaria can affect the nutritional status of children. A study conducted in the rural community of Amazonian region indicated that children who suffered malaria episodes presented worse anthropometric parameters [23]. Likewise, in a study carried out in a holoendemic malaria area of Tanzania, catch-up growth was seen in those children who used ITNs [12], which suggests that Plasmodium infection plays a role in the aetiology of malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to those of many other studies, which have reported that malaria can affect the nutritional status of children. A study conducted in the rural community of Amazonian region indicated that children who suffered malaria episodes presented worse anthropometric parameters [23]. Likewise, in a study carried out in a holoendemic malaria area of Tanzania, catch-up growth was seen in those children who used ITNs [12], which suggests that Plasmodium infection plays a role in the aetiology of malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…This finding revealed that severely malnourished children with no malaria infection recovered early compared to children with malaria infection. This is supported by studies conducted in Niger, Amazon, and Rwanda [25,31,32]. The reason might be that malaria impairs gluconeogenesis and increases energy consumption, induces malabsorption, predisposes one to loss of immunity, and results in inability respond to standard treatments [32,33].…”
mentioning
confidence: 88%
“…In Vanuatu, during the 6-month period before nutritional assessments, the incidence of P. vivax malaria was significantly higher among the underweight and wasting children than among healthy children (13) . Actually, for vivax malaria and undernutrition, the results suggest a monotonic relationship, i.e., more malaria episodes (14) or shorter periods until the nutritional measurement (14) (15) lead to greater likelihoods of underweight, wasting, and impaired growth in children. Vivax malaria led to decreases in ponderal velocity of 138.6, 108.0, and 61.0 g/episode over 2, 4, and 6 months, respectively (15) .…”
Section: ) Biological Gradientmentioning
confidence: 92%
“…In Vanuatu, having P. vivax malaria within the previous 6-month period was a major predictor of underweight [weight/age, Z < -2; adjusted odds ratio (aOR), 2.4; 95% confidence interval (CI), 1.3-4.4; p = 0.006] and wasting (weight/height, Z < -2; aOR, 2.7; 95% CI, 1.4-5.2; p = 0.004) in children, after adjusting for age, sex, season, birth weight, parity, and α-thalassemia genotypes in a multiple logistic regression model (13) . In the Brazilian Amazon, among children who had vivax malaria (aOR, 4.0; 95% CI, 1.4-11.4; p = 0.008) and a period of 6-12 months between the last malarial episode and the second nutritional assessment (aOR, 4.4; 95% CI, 1.3-15.3; p = 0.020), there was a significant association with increased odds of inadequate growth velocity, after adjusting for the a priori-defined variables of age, sex, maternal education, and socioeconomic status (14) . These data support a non-negligible strength of association between vivax malaria and undernutrition in endemic areas.…”
Section: ) Strengthmentioning
confidence: 93%
See 1 more Smart Citation